Assessment of Key Performance Indicators of the Primary Health Care in Oman: A Cross-Sectional Observational Study. (August 2020) - Al Rashidi, Badria; Al Wahaibi, Ahmed H.; Mahomed, Ozayr; Al Afifi, Zainab; Al Awaidy, Salah
Objective: Effective primary health care (PHC) is the key to attaining universal health coverage. The key performance indicators (KPIs), is a component of quality improvement in the PHC service sector that provides feedback to inform and better public service delivery and promoting accountability. We assessed the current performance of PHC service by using KPIs to identify the possible challenges that necessitate being confronted, highlight the lessons learnt, and propose steps towards improvements. Methods: We conducted a cross-sectional observational study across 12 PHC centers in 6 governorates in Oman during the period of June 2017 to June 2018. Secondary data from the computerized medical records of the PHC centers on six key indicators, accessibility, workload, outcomes, timeliness, satisfaction, and safety were analysed to assess the performance of PHC service and to identify challenges confronted and propose steps towards further service improvement. Results: The mean overall KPIs scores across the ten PHC centers were 174.5 (SD: 9.80) or 67.01%. The overall scores were normally distributed with a median score of 175 (IQR: 171-181). The lowest percentage score was obtained by Al Qabil (61.35%) with the highest mark being at Wadi Kabir (70.54%). The mean score across all KPIs was 3.84 (SD:0.94) with a median score of 3.9 (IQR: 3.43-4.5). Of the six KPI components, safety (4.85), satisfaction (4.67), timeliness (4.44), and accessibility (4.31) had the highest performance scores, whilst workload (4.15) and outcomes (3.75) lagged behind. Conclusions: Performance across the KPIs exhibited a considerable variation between facilities, with workload and outcome performing lower than other components. The findings of this study offered a measure of internal strengths that need to be sustained, challenges that require quality improvement initiatives, and external factors such as social determinants that impact overall performance PHC.